Perinatal pathology: the role of the clinical pathological dialogue in problem solving - Faa, Gavino; Fanos, Vassilios; Van Eyken, Peter (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2014)
Pathologists and clinicians come together and exchange views, they instil in one another doubts, they break down barriers. Asphyxia, respiratory distress, sepsis, multi-organ failure (MOF), cerebral ischemia and neuroprotection, necrotizing enteritis, renal and biliary pathology (including congenital nephrotic syndrome), injury caused by drugs, cardiac decompensation, placental pathology, neonatal issues in mothers with tumor: these are the topics debated, in the true sense of the word, by perinatologists and pathologists. In some pathologies (e.g. MOF) the pathophysiology is surprisingly the same in the neonate and the adult. Different disciplines deal for example with immunohistochemistry and metabolomics with the processing of thousands of data in search of something that cannot be found with the classic criteria of anamnesis, objective examination, laboratory tests and imaging. Big data and information science promise to change the world. To come to grips with the extreme biological complexity of our organism and each of our organs, the completeness of enormous amounts of data is of extraordinary value if assessed holistically with the “omic” disciplines. Thus we have the possibility of understanding our extraordinary interindividual variability. The new technologies and their application do not diminish the role of physicians: on the contrary, they represent a formidable instrument for extending their diagnostic potential and make possible 5-P medicine: personalized, prospective, predictive, preventive, participatory. Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken